Early evolutionary divergence between papillary and anaplastic thyroid cancers. (10th April 2018) - Capdevila, J; Mayor, R; Mancuso, F M; Iglesias, C; Caratù, G; Matos, I; Zafón, C; Hernando, J; Petit, A; Nuciforo, P; Cameselle-Teijeiro, J M; Álvarez, C; et al.
Abstract: Background: Papillary thyroid cancer (PTC) is the most common thyroid carcinoma and exhibits an almost uniformly good prognosis, while anaplastic thyroid cancer (ATC) is less frequent and is one of the most aggressive cancers usually resistant to conventional treatment. Current hypothesis posits that ATC derives from PTC through the progressive acquisition of a discrete number of genomic alterations and implies that the mutational landscape of ATC resembles that of PTC. However, the clinical behaviour of ATC and PTC is radically different. We decided to address the disconnection between the clinical behaviour of ATC and PTC and the proposed model of the progressive development of ATC from PTC. Patients and methods: We carried out exome sequencing of DNA from 14 ATC specimens including three cases of concomitant ATC and PTC as well as their corresponding normal DNA from 14 patients. The sequencing results were validated using droplet digital PCR. We carried out immunohistochemistry and immunofluorescence studies of the concomitant ATC and PTC cases. In addition, we integrated our sequencing results with the existing TCGA data. Results: Most of the somatic mutations identified in the ATC component differed from the ones in PTC in the cases of concomitant ATC and PTC. The trunks of the phylogenetic trees representing the somatic mutations were short with long branches. In one case of concomitant PTC and ATC specimens, we observed an infiltration of PTC cells within the ATC component. Moreover, we integrated our results with data obtained from TCGA and observed that the most frequent mutations found in ATC presented high cancer cell fraction values and were significantly different from the PTC ones. Conclusion: ATC diverge from PTC early in tumour development and both tumour types evolve independently. Our work allows the understanding of the relationship between ATC and PTC facilitating the clinical management of these malignancies.